Effectiveness of an information booklet on knowledge regarding breastfeeding among mothers of under two-years children - Nag, Arpita; Chaturvedi, Anjali; Kumari, Rina (International Journal of Contemporary Pediatrics, 2021)
Background: The basic food of infant is mother’s milk. Breastfeeding is the most effective way to provide a baby with a caring environment and complete food. It meets the nutritional as well as emotional and psychological needs of the infant. But there is tendency to replace the natural means of infant feeding and introduction of breast milk substitutes. So, breastfeeding deserves encouragement from all concerned in the welfare of children. Methods: A quantitative evaluative research approach and Quasi experimental one group pre-test post-test design was used. By using purposive sampling technique total 65 mothers of under two years children admitted in selected wards i.e.; pediatric and maternity ward at V.P.I.M.S., Lucknow, were selected to assess the effectiveness of an information booklet on knowledge regarding breastfeeding. Written permission was obtained from the authorities of Vivekananda Polyclinic and Institute of Medical Sciences, Lucknow, where the study was conducted. Results: In pre-test the majority of mothers, 50.80% had moderate knowledge, 40.00% of mothers had inadequate knowledge whereas 9.20% of mothers had adequate knowledge. In post-test majority 92.30% mothers had adequate knowledge, 7.70% mothers had moderate knowledge whereas none of the mothers had inadequate knowledge. Conclusions: The study concluded that after the distribution of information booklet on knowledge regarding breastfeeding mothers of under two-years children have gained their knowledge.